Adolescents in Secure Accommodation in Scotland: Exposure and Impact of Traumatic Events. Issue 7 (9th August 2018) - Barron, Ian; Mitchell, David
ABSTRACT: The current study sought, for the first time, to assess the nature of trauma exposure and resultant symptoms in adolescents ( n  = 17) in secure accommodation in Scotland. A case study mixed methods design involved analysis of case files, trauma history interviews, and standardized trauma symptom questionnaires with adolescents and program staff in 1 facility. A developmental trauma framework was applied to file analysis. Despite extensive abuse and resultant symptoms identified in files, few explicitly reported traumatization. Adolescents in interview, however, reported numerous domestic and institutional traumatic events. High levels of posttraumatic stress (65%), depression (65%), and dissociation (18%) were identified. It appears adolescent traumatization is pervasive in 1 secure accommodation facility in Scotland. Studies across Scotland's secure facilities are needed to assess reliability of findings. Indications are that staff in secure accommodation need to have an understanding of trauma exposure, resultant symptoms, and how to respond to traumatized adolescents.